Effect of low molecular weight component on the melting and crystallization behavior of poly(ether ether ketone) from a rheological insight - He, Huiwen; Zeng, Xiaoqiang; Ma, Meng; Shi, Yanqin; Zhu, Yulu; Shi, Haibin; Chen, Si; Wang, Xu (Polymer engineering and science, 2025)
Low molecular weight components significantly influence the crystallization behavior of polymers, particularly rigid backbone polyaromatic ether ketones (PEEK), while the mechanism remains unclear. Herein, to investigate the effect of low molecular weight components on the crystallization behavior of PEEK, a commercial narrow molecular weight distribution PEEK (N‐PEEK, Mn/Mw = 1.1) resin was blended with a specific amount of broad molecular weight PEEK (B‐PEEK, Mn/Mw = 1.9) resin. The change in the molecular weight distribution of the blend is mainly attributed to the variation in the content of low molecular weight components. Non‐isothermal crystallization kinetics of the blends were analyzed by the Jeziorny model and the Mo model, and it was found that the low molecular weight components increased the initial crystallization temperature of PEEK and accelerated the non‐isothermal crystallization rate; meanwhile, the crystal structure was preserved, which was proved by X‐ray diffraction (XRD). Furthermore, dynamic rheological tests were conducted to study the nucleation and growth processes. The changes in viscosity or modulus during the crystallization process indicated that the low molecular weight components accelerated the nucleation rate, reduced the crystallization induction time, and facilitated molecular chain movement during the growth process. Highlights Low molecular weight component improves crystallization rate and crystallinity. Rheology supports DSC, revealing impacts on nucleation and crystal growth. Crystallization temperature rises while keeping the crystal structure intact. Taking the molecular weight distribution as the primary research subject. The nucleation and growth stages are analyzed by dynamic rheological tests and proved that the low molecular weight component significantly promoted both the nucleation rate and growth rate of PEEK, while markedly shortening the induction time of crystallization.